Centering Transborder Students: Perspectives on Identity, Languaging and Schooling Between the U.S. and Mexico. (3rd April 2017) - Kleyn, Tatyana
Abstract : Undocumented families' rates of repatriation to Mexico from the United States have risen throughout the Obama administration, and this trend will likely increase under Donald Trump. This study describes the experiences of Mexican-born youth who grew up in the United States and are back in Mexico. While these children are participants in their families' migration, their input is rarely sought in decisions to leave or return to a country. This article shares transborder students' voices on their struggles to find their identities as Mexican, American, or some combination of the two. They reflect on their schooling experiences across countries, and how these challenges are compounded when they are new to learning in Spanish or indigenous languages in Mexico.